Study of correlation between the gender gap index, economic efficiency, and governance in European countries - Nazar Podolchak; Volodymyr Martyniuk; Natalia Tsygylyk (Contemporary Economics, 2023)
As gender equality is a priority for 17 sustainable development goals, it is appropriate to establish a correlation between the Gender Gap Index (GGI), economic efficiency and governance. Three hypotheses have been investigated. It is established that there is no general direct relationship between the level of GGI and GDP per capita growth (annual) for all countries, regardless of their level of development. In the UK, small fluctuations in GDP per capita growth (annual) do not affect GGI levels; however, the Covid-19 pandemic does have its impact. In Germany, any fluctuations in GDP per capita growth (annual) do not affect the level of GGI, yet it is affected by changes in population, in particular by increasing migration. In Ukraine, significant fluctuations in GDP per capita growth (annual) do not affect the level of GGI, although this index is reduced by the effects of the pandemic a year after its onset. In addition, the relationship between the population, civil servants, their distribution by sex, average wages and GDP per capita growth (annual) and, consequently, the welfare of the population of these countries was established. The obvious efficiency of the UK's and Germany's strategic governance systems has different implications for achieving gender equality and well-being. It is proposed to use the Windmill economic model to achieve gender equality among civil servants in the developing country.
Keywords: J16; J18; 330; civil service; economy; gender equality; Gender Gap Index; public administration